Optimization of Digital Business to Support MSMEs Growth in the Industry 4.0 Transformation - Aswadi Jaya; Farhan Saputra; Derlina; Dwi Nur Ramadhan; Thomas Green (CORISINTA, 2026)
Digital transformation has become essential for Micro, Small, and Medium-Sized Enterprises (MSMEs) in the Industry 4.0 age in order to improve resilience and competitiveness in spite of restricted resources. The influence of digital optimization techniques on MSME growth is investigated in this study. These tactics include digital marketing adoption, e-commerce platform usage, and digital financial management tools. Data from 100 MSMEs was gathered quantitatively using structured questionnaires, and the correlations between the variables were examined using SmartPLS 3. E-commerce platform usage has the biggest impact, followed by digital financial management tools and digital marketing adoption, according to the results, which show that all digital strategies have a favorable impact on MSME growth. According to the model's R Square value of 0.694 for MSME Growth, the examined strategies account for around 69.4% of the growth variation. These results demonstrate how crucial it is for MSMEs to embrace digital technology in order to increase their market reach, boost operational effectiveness, and fortify financial management. Future research is urged to examine other factors impacting digital adoption and to apply these findings in a variety of sector scenarios. The study concludes that MSMEs must invest in digital skills in order to achieve sustainable development in a competitive digital world.